Collaboration of Hprt/K-RAS/c-Myc mutation in the oncogenesis of T-lymphocytic leukemia: a comparative study - Mai O Kadry; Abdel-Hamid Z Abdel Hamid; Rehab M Abdel-Megeed (Future Science OA, 2024)
Aim: Leukemia is a malignant clonal illness stem from the mutations of hematopoietic cells. Acute lymphoblastic leukemia is one of the utmost prevalent kinds of leukemia, is brought on by atypical lymphoid progenitor cell division in the bone marrow. Materials & methods: A comparative study between, titanium Nanoparticle-loaded doxorubicin or cisplatin and lactoferrin-loaded doxorubicin or cisplatin, on 7,12-dimethylbenz[a]-anthracene (DMBA)-induced leukemia was investigated and confirming the hypothesis that messenger RNA of Hprt/K-RAS/c-Myc/SAT-2/P53/JAK-2 is a forthcoming signaling pathways in leukemia. Results: A significant alteration in Hprt, K-RAS, C-Myc, P53, JAK-2 and SAT-2 genes was observed post DMBA intoxication the aforementioned Nanodrugs modulated these signaling pathways. Conclusion: The carrier-loaded drugs triggered cytotoxicity of cancer cells via enhancing drug efficacy and bio-availability.